Large-scale solar water heating in South Africa: Status, barriers and recommendations. (November 2016) - Joubert, E.C.; Hess, S.; Van Niekerk, J.L.
Abstract: This work evaluates large-scale solar thermal systems in South Africa. A database of 89 systems has been generated and analysed with regards to cost, applications and beneficiary industries. Since 2007 the average total annual commissioned collector area was only 1544 m 2 . Most systems are used for domestic hot water preparation. The average system cost is currently 603 EUR/m 2, which is higher than the costs achieved in other countries. A brewery solar process heat case study compares 10 proposals for a tender. Proposed system installation costs varied by a factor of 2.5, suggesting low maturity in this market. The winning proposal has a 120.7 m 2 gross collector area, LCOH = 7.9 EURc/kWh, IRR = 16.7% and payback = 9.3 years. A key barrier is the low cost of coal of 2 Eurocent/kWh, which is the dominating fuel. Current systems can already well compete with heat sources like paraffin, diesel, petrol and gas, which is shown by a detailed financial analysis. Besides the low coal price, other key barriers for increased market diffusion are long payback times, the technical complexity of the technology, as well as the lack of awareness and trust in the technology. Highlights: A database of 89 large-scale solar thermal systems in South Africa is analysed. Hot water preparation is the main application and the average cost is 603 EUR/m 2 . A brewery solar process heat case study compares 10 proposals for a tender. The winning proposal has LCOH = 7.9 EURc/kWh, IRR = 16.7% and payback = 9.3 years. A key barrier for solar heat is the low cost of coal, the dominant fuel.